Post-Surgical Hypoparathyroidism: Assessment of Risk Factors and Prevention Strategies Following Thyroidectomy - Ridha, Ali Mohammedali (American Journal of Biology and Natural Sciences, 2025)
The aim of this study was to evaluate the key risk factors for postoperative hypoparathyroidism in thyroidectomized patients and to establish evidence-based methods of its prophylaxis. A retrospective cohort study was conducted, reviewing electronic health records of patients who had total or near-total thyroidectomy. Demographic data, surgical features, and biochemical data postoperatively were extracted. The findings revealed age, type of surgery (total thyroidectomy), and surgeon experience to be significant predictors of need of postoperative calcium and vitamin D supplementation. Older patients and total thyroidectomy were more likely to require supplementation. Improved surgical techniques, and in particular identification of the parathyroid nuclei, were also linked with better outcomes along with experience of the surgeon. The study reinforces the need for individualised postoperative care, highlighting the importance of flexible management approaches being based on each patient's individual risk profile, such as age and the surgical type performed, in order to achieve the best possible outcome. These results add to the current literature on complications of thyroidectomy and show that the occurrence of hypoparathyroidism and patient recovery can be significantly improved with optimised surgical practice and post-operative management protocols. The implications of the study range from clinical guidelines and the further development of evidence-informed practices regarding operative management of postoperative complications.